Nutritional Composition, Pigment Profiling, and Antioxidant Capacity of Locally Produced Powdered Spirulina from Central Java, Indonesia - Elma Alfiah; Sri Anna Marliyati; Mira Dewi; Mokhamad Fahrudin (Journal of Health and Nutrition Research, 2026)
Spirulina (Arthrospira sp.) is widely recognized as a nutrient-dense microalgal biomass with potential functional properties. This study aimed to characterize the nutritional composition, bioactive pigment profile, and antioxidant activity of locally produced spirulina powder from Central Java (Indonesia), with particular emphasis on its radical scavenging capacity evaluated using the DPPH assay. Spirulina powder was analyzed for proximate composition (moisture, crude protein, crude fat, carbohydrate, and ash), as well as major bioactive pigments including phycobiliproteins, chlorophyll, and β-carotene. Antioxidant activity was determined using the DPPH radical scavenging assay. The spirulina powder contained 56% protein. The bioactive pigment profile was dominated by phycobiliproteins, particularly C-phycocyanin, alongside high levels of chlorophyll and β-carotene. Antioxidant evaluation showed a concentration-dependent DPPH radical scavenging activity, with an IC₅₀ value of approximately 396 ppm, indicating moderate direct radical scavenging capacity within the DPPH system. These findings suggest that local spirulina from Central Java possesses limited instantaneous free radical scavenging activity when assessed using a single-mechanism chemical assay. However, its complex nutritional matrix may contribute to antioxidant mechanisms beyond direct radical neutralization, although this was not specifically evaluated in the present study.